Public preference between Islamic and conventional financing: a study in Penampang, Sabah / Shasha Fariah Mohd Shahlan Abdullah - Mohd Shahlan Abdullah, Shasha Fariah (2014)
Islamic Finance governed by the Shariah (Islamic Law), sourced from Quran and Sunnah. Islamic finance was started in Malaysia of 1963 when the government established Tabung Haji of Pilgrims Management and Fund Board. It was established to invest the saving the local Muslims with no interest (free interest). According to Keong,Khor,Low& Wong (2012) islamic banking conduct of banking based of Syariah principle which not allow the existence the interest in operation while promoting the product such as profit-sharing (Mudharabah). It also purposes the awareness of Islamic Banking product and services among the Non-Muslims in Malaysia. The key principle of Islamic is the sharing of profit and loss ( equity participation), prohibition of R/'bathat consider as haram (non-permissible),and last the Syariah must be approved activities. Compare to the Conventional banking,was the first to be incorporated in Kuala Lumpur (Kwong Yik Banking Corporation) in July 1913. Then by the 1917, branches of Singapore-incorporated bank established branches in Malacca and Muar. Currency Board was establishing in 1907 to issue currency and protect its value. By the time 1959, the Central Bank of Malaya was established that called Bank Negara Malaysia under the Central Bank of Malaya Ordinance. The different between Islamic and Conventional is that according to Ust Hj Zaharuddin Hj Abd Rahman (2007), lslamic is based on the Shariah which all the dealing with transaction, business approach, investment focus on products,responsibility will derived from the Shariah Law need to be faith and must stay the limit of Islamic Law or Shariah. Meanwhile for the conventional, is based on the debtor-creditor relationship between the depositors and the banks, or between the bank and borrowers on the other.